2001
DOI: 10.1097/00002030-200106150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV disease progression by injection drug use and by sex in the era of highly active antiretroviral therapy

Abstract: Disease-free survival time was extended with the use of HAART, but these gains were not equally distributed by sex and IDU in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 22 publications
8
83
0
Order By: Relevance
“…Some studies showed that CD4+ T-cell count, viral load, and IDU were predictors of survival time. These studies were consistent with our finding, in which CD4+ T-cell count less than 200 was significant effect on survival, but in-contrast with our result, IDU was not independent statistically significant predictor of mortality [22][23][24]. Based on the study conducted by Larsen et al, the risk of HIV-related death was not increased in IDUs compared to non-IDUs.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies showed that CD4+ T-cell count, viral load, and IDU were predictors of survival time. These studies were consistent with our finding, in which CD4+ T-cell count less than 200 was significant effect on survival, but in-contrast with our result, IDU was not independent statistically significant predictor of mortality [22][23][24]. Based on the study conducted by Larsen et al, the risk of HIV-related death was not increased in IDUs compared to non-IDUs.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in vitro and animal studies found immunosuppressive effects of opiates, cocaine and other illicit substances [24][25][26][27][28][29][30]. Since 1996, combination ART has largely determined the outcome of HIV infection in patients with access to care [16], and mortality was found to be substantially reduced after the introduction of potent ART also among IDUs [31][32][33]. Therefore, drug addiction treatment programmes, which make access to somatic care possible, appear to be an important prerequisite for improved outcome of ART.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have demonstrated the negative effect of alcohol 24 and illicit drugs on access to and adherence with ART, [25][26][27][28][29][30][31][32][33] this small pilot study suggests that gaining access to ART in a trusted setting may promote positive health behaviors (e.g., seeking and gaining access to drug treatment) and result in improved health outcomes among active drug users. In our study, the proportion of individuals who achieved an HIV-1 RNA level below the level of detection and an increase of the CD4 lymphocytes count is similar to results obtained in clinical trials in highly selected non-IDU patients.…”
Section: Discussionmentioning
confidence: 73%